Clinical Approach to Chronic Pancreratitis - Tri Juli Edi T; Marcellus Simadibrata; Murdani Abdullah (The Indonesian Society for Digestive Endoscopy, 2003)
Chronic pancreatitis is still considered an uncertain process with an undetermined pathogenesis and ill defined treatment. Chronic pancreatitis is distinguished from acute pancreatitis based on structural and functional differences. In acute pancreatitis, the gland is normal prior to the attack, and returns to normal after an acute attack, while in chronic pancreatitis, the gland is already in an abnormal state prior to or following an attack or prior to and following an acute attack. The most common local complication of chronic pancreatitis is the formation of pseudocysts. Psedocysts are usually formed due to passage obstruction of the pancreatic tract (retention cyst) or due to recurrent acute exacerbation Several pancreatic abnormalities, such as stones, ductal stricture, fluid collection, and functional sphincter abnormality, could be treated using endoscopy. Adjuvant treatment for biliary duct abnormality such as biliary stricture due to pancreatitis, and stent insertion in cases of duodenal obstruction, could also be performed via endoscopy Keywords: Chronic pancreratitis, tropical pancreatitis, treatment